USING SIMULATION TO MOTIVATE SPEAKING SKILL IN BUSINESS ENGLISH CLASSROOM - Wienny Adriyati (Soegijapranata Catholic University, 2010)
Teaching English for Specific Purposes (ESP) should be intendedfor communicative functions. This implies that teaching English is to enable students to acquire knowledge and skills to communicate effectively. Language learning seems to occur most effectively when students have opportunities to use the language. Theidea to use simulation in teaching English is considering students who are not motivated to study English in Business English class and it is meant to create interactive classes. Therefore,they areguided to create the situation where they can use the language. In fact, the students are claimed to master English either passively or actively for their future benefit after they graduate from their study. When they graduate they not only master their major study but also expert in using English for communication. In this article it isproposed some examples of simulation that are effective in business English classes; making business plan, conducting meeting, doing negotiation and presentation. To apply the simulation, the students are asked to make a roleplay. After the simulation is conducted, it is expected that the students are able to use the language interactively and creatively.